Cost-effective monitoring algorithm for cyber-physical system platform using combined spatio-temporal model - Choi, Kwanghoon; Lim, Sung Hwa; Kim, Jai Hoon (Journal of Supercomputing, 2018)
Cost-effective schemes are essential in cyber-physical system to gather a huge amount of data from physical system in real time. In general, sensor networks monitor the physical system and transfer the data to cyber system which analyzes the data and provides many kinds of useful services for users and controls physical system. Sensors, as elements of ubiquitous sensor networks, have very limited resources (power capacity, processing power, and networking capability). Therefore, in the absence of energy-efficient mechanisms for ubiquitous sensor networks, the network life time will be reduced. In this paper, we present a cost effective monitoring scheme for cyber-physical system platform using spatio-temporal model. Our proposed model combines space and time domains. Sensor data are sent only when data are changed in both space and time domains. If the data are not changed in any domain then the previous data (time domain) or neighboring data (space domain) are used without additional communication cost. We also analyze and compare cost between periodic and aperiodic monitoring model. Using the analysis, we can choose the proper model (periodic or aperiodic) according to cyber-physical system parameters.
Keywords: Communication cost; Cost modeling; Cyber physical systems (CPSs); Monitoring algorithms; Network life time; Spatio temporal; Spatio-temporal models; Ubiquitous sensor networks; Cost model; Cyber physical systems; Sensor network; Spatio-temporal